Divestment and privatization in Guyana, revisited - Thomas, Clive Y. (Univ. of Guyana. Institute of Development Studies GeorgetownGY, 1993)
Looks at a few general macro-economic issues. Examines certain aspects of the divestment record using the Guyana Telephone and Telegraph Company as an example. Looks at the future bearing in mind the announced intention of government to divest the sugar industry before the 1992 national elections.